2006
DOI: 10.1152/ajpregu.00644.2005
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced sympathetic reactivity associates with insulin resistance in the young Zucker rat

Abstract: Somatosympathetic reflexes were studied in young hyperinsulinemic, insulin-resistant (Zucker fatty) rats (ZFR) and a related control (Zucker lean) strain (ZLR). Glucose metabolism was characterized by minimal model analysis of intravenous glucose tolerance test data. Seven-week-old ZFR (n ϭ 18) and ZLR (n ϭ 17) were studied under pentobarbital anesthesia. Mean body weight and plasma glucose and insulin concentration were significantly greater (P Ͻ 0.05) in ZFR than in ZLR, whereas basal values of mean arterial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
22
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 50 publications
6
22
0
2
Order By: Relevance
“…In contrast, blood glucose concentration in non-treated obese rats remained high for at least 120 min (172.4 ± 1.3 mg/100 mL; P b 0.0005), and significantly different from all the other groups at this time point, as expected considering their typical glucose intolerant and insulin resistant profile [52].…”
Section: Vo(dmpp) 2 Completely Reverts the Glucose Intolerant Profilesupporting
confidence: 62%
“…In contrast, blood glucose concentration in non-treated obese rats remained high for at least 120 min (172.4 ± 1.3 mg/100 mL; P b 0.0005), and significantly different from all the other groups at this time point, as expected considering their typical glucose intolerant and insulin resistant profile [52].…”
Section: Vo(dmpp) 2 Completely Reverts the Glucose Intolerant Profilesupporting
confidence: 62%
“…However, we would suggest that these mild increases in BP exhibited in OZRs (29,41) and the short period of "hypertension" do not likely contribute to the severe impairment in AA metabolism and functional vasodilation. Indeed, a recent study (45) in OZRs showed that insulin resistancemediated stimulation of the sympathetic nervous system is related to altered glucose metabolism before the onset of hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…At 7 wk of age, fasted OZR have elevated plasma levels of triglycerides and insulin (12,35,42). Although reports of differences in fasted levels of blood glucose between OZR and LZR at 7 wk are inconsistent, insulin resistance is unmistakable as evidenced by the hyperinsulinemia and impaired glucose tolerance (12,35,42). By adulthood, OZR have fasting hyperglycemia with elevated blood cholesterol and nonesterified fatty acids compared with juvenile OZR and age-matched LZR (12,37).…”
Section: * *mentioning
confidence: 99%